STRUCTURAL INEQUALITY IN THE THIRD SECTOR: HOW LAW AND LEGISLATIVE DRAFTS PRODUCE, SUPPORT AND ORGANIZE HIERARCHICAL SYSTEMS AMONG NON-GOVERNMENTAL ORGANIZATIONS - A. Pronin; D. Skibo (BRICS Law Journal, 2016)
Within the framework of the article the problem of inequality in the Third Sector is defined. The authors tie the production and institutionalization of this inequality with laws that were passed in the sphere of the regulation of non-governmental organizations (NGOs) in recent years as well as with several draft laws. The analysis focuses on the “foreign agent” status. Organizations that receive this status have more obligations and fewer rights in comparison with other NGOs. According to the research, the burden of a foreign agent status can be measured in terms of legal discrimination, but it also may be measured financially. The authors see fit to analyze other existing legal statuses of Russian NGOs, above all the status of an NGO realizing socially valuable projects (SO NGO), and to compare them with the legal status of a “foreign agent” NGO. The analysis shows that foreign agent NGOs and SO NGOs gradually stand at opposite poles of the legal system: the former are synonymous with politically and legally undesirable subjects, whereas the latter step by step become the state-oriented, useful organizations meriting additional support, protection and social, economic and legal benefits.